Estudio de riesgos físicos por ruido y vibraciones en la central hidroeléctrica Pucará. - Paucar Ramos, John Estalin (2020)
This research project focuses on the study of physical risks due to noise and vibrations in the hydroelectric power plant Pucará, which has as main objective to evaluate the levels of daily exposure, by collecting information on the characteristic of jobs exposed to these risks, it could be evidence the main sources that directly affect the jobs. The noise mediations were made accoroling to the norm NTEINEN-ISO 9612, using a class 2 sound level meter for levels of exposure to daily noise with “A” weight, the norm NTE INEN-ISO 2631, using a 3 axis vibrometer, daily exposure levels, daily exposure levels are compared to limits permitted by Executive decree 2393 and the norm NTP 839. The proposed activities were achieved by determining jobs with possible noise and vibration events, this was achieved through a physical risk identification matrix and the elaboration of matrices in Excel for data collection and evaluation of results. In carrying out the noise assessment it was observed that only one job has a level of daily noise exposure with “A” weighting of 91,6 dB with weighting “A” being the level higher that 85 dBA established by Executive Decree 2393 of the level of exposure to 8 hours of daily work, the other jobs evaluated are at a tolerable risk. In the evaluation of exposure levels for whole body vibrations, it was determined that workstation are below 0,5 m/s2 , this being the limit allowed to result in corrective action. Finally, preventive and corrective measures were put in place for risk assessed jobs intolerable.